Metastasis to the appendix from adenocarcinoma of the ascending colon: A case report. Issue 11 (March 2017) - Li, Yingjie; Li, Mingshan; Li, Xiaoxia; Sang, Haiquan
Abstract: Rationale: Metastasis of cancer cells involves shedding from the primary tumor through various means to distant tissues and organs with continued growth and formation of new metastatic tumors of the same cancer type as the original tumor. The common sites for colon cancer metastases include the pelvis, retroperitoneal lymph nodes, liver, and lungs; Colon cancer metastases to the appendix are rare, as reported in this case. Patient concerns and diagnoses: A 45-year-old man was admitted to our department with a 24-hour history of abdominal distension and incomplete obstruction. Colonoscopy showed an elevated lesion in the ascending colon and the pathologic diagnosis was adenocarcinoma. Interventions and outcomes: This patient underwent a radical right hemi-colectomy. The post-operative pathologic examination revealed metastatic adenocarcinoma in all layers of the appendix, especially the muscularis mucosae. The diagnosis was adenocarcinoma of the ascending colon (pT4bN2bM0 stage IIIC) with metastatic adenocarcinoma of the appendix. Lessons: An absent right colic artery with lymph node fusion might increase the risk of appendiceal cancer metastasis.